Strong constraints on the b → sγ photon polarisation from B0 → K*0e+e− decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Brandt, Jonathan; Dziewiecki, Michal; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2020)
An angular analysis of the B0 → K*0e+e− decay is performed using a data sample corresponding to an integrated luminosity of 9 fb−1 of pp collisions collected with the LHCb experiment. The analysis is conducted in the very low dielectron mass squared (q2) interval between 0.0008 and 0.257 GeV2, where the rate is dominated by the B0 → K*0γ transition with a virtual photon. The fraction of longitudinal polarisation of the K*0 meson, FL, is measured to be FL = (4.4 ± 2.6 ± 1.4)%, where the first uncertainty is statistical and the second systematic. The $$ A_{T}^{Re} $$observable, which is related to the lepton forward-backward asymmetry, is measured to be $$ A_{T}^{Re} $$= −0.06 ± 0.08 ± 0.02. The $$ A_{T}^{(2)} $$and $$ A_{T}^{Im} $$transverse asymmetries, which are sensitive to the virtual photon polarisation, are found to be $$ A_{T}^{(2)} $$= 0.11 ± 0.10 ± 0.02 and $$ A_{T}^{Im} $$= 0.02 ± 0.10 ± 0.01. The results are consistent with Standard Model predictions and provide the world’s best constraint on the b → sγ photon polarisation.